Anomalous increase in modulus upon hydration in random copolymers with hydrophobic segments and hydrophilic blocks - Kohn, J. (2013)
The polymers with hydrophilic moieties typically become soft upon hydration. Here we report an exception to this rule. The modulus was found to increase upon water uptake in polymers in which hydrophilic poly(ethylene glycol) (PEG) segments were incorporated randomly into a chain of hydrophobic segments of 3,5-diiodo desaminotyrosyl-tyrosine ethyl ester. The Young's modulus of the copolymer increased by as much as 15-fold upon hydration with 30 to 60 vol% of PEG. This increase in modulus was fully reversible and was observed at both 22 °C and the physiological temperature of 37 °C. A degree of hydration of 3 water molecules per ethylene glycol and hydration-induced phase separation of hydrophilic domains appear to be essential for the observed increase in modulus. This stiffening effect is attributed to the PEG segments in the hydrated domains that no longer participate in the transfer of stress through the polymer matrix as they do when they are molecularly dispersed along the polymer chain in the dry state.